STRATEGI BENCHMARKING DALAM MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA DI SEKOLAH - al Kamil, Said; Putridiyanti , Fita (Universitas Nurul Jadid, 2020)
This paper intends to analyze the principal's benchmarking strategy in improving the quality of human resources at SMA Nurul Jadid, Paiton, Probolinggo in an institution, namely to develop competitiveness. The method used is a qualitative approach through case studies So that it can encourage the quality of good institutional resources. This research provides strategic implications for benchmarking institutions in order to meet the complexities of the demands of the community in Islamic boarding schools to equalize those of high schools outside the pesantren. Even higher quality. As for the efforts made by Nurul Jadid Senior High School in improving the quality of human resources by increasing foreign language skills, Class Acceleration Provide motivation to every school member to continue to improve their performance to match the expectations of all parties. So that the quality of human resources in an institution can be created.